1969
DOI: 10.1063/1.1658187
|View full text |Cite
|
Sign up to set email alerts
|

Formation and Growth of Tarnish on Evaporated Silver Films

Abstract: We have studied the growth of the silver sulfide tarnish film which forms on silver deposited on smooth, amorphous substrates and rough and smooth polycrystalline substrates. Both ellipsometric and electron-microscope techniques were used to measure the average thickness of the tarnish films. The growth rate was found to be variable depending on the concentration of the sulfurous gases. In normal laboratory air (measured concentrations of H2S and SO2 less than 0.2 parts per billion) a 1-Å-thick tarnish film ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
115
0

Year Published

1970
1970
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 154 publications
(117 citation statements)
references
References 28 publications
2
115
0
Order By: Relevance
“…In order to transfer and expose the desired metal surface after evaporation, the sample is glued with the vacuum silver side (fiber optic grade epoxy, EpoTek 377, EpoTek) to another cleaned piece of Si wafer, and the epoxy cured at 150°C for 30 min. To minimize the effect of surface oxidation [65], samples are then stripped to expose the Ag film but only shortly before the measurement.…”
Section: Methodsmentioning
confidence: 99%
“…In order to transfer and expose the desired metal surface after evaporation, the sample is glued with the vacuum silver side (fiber optic grade epoxy, EpoTek 377, EpoTek) to another cleaned piece of Si wafer, and the epoxy cured at 150°C for 30 min. To minimize the effect of surface oxidation [65], samples are then stripped to expose the Ag film but only shortly before the measurement.…”
Section: Methodsmentioning
confidence: 99%
“…Their Raman bands, which appear around 188, 243, and 273 cm -1 for Ag 2 S and 432, 460, 595, 623, 970 (strong), and 1079 cm -1 for Ag 2 SO 4 [2], can coincide with spectral regions of interest such as the radial breathing mode of carbon nanotubes (CNT) [3]. It was also shown that the electric field enhancement decreases with the aging of the silver surface [4]; the thickness of Ag 2 S increases over time as it is not a self-limiting process confined to the surface [5]. Thus, experiments with silver probes are almost exclusively performed on the day of the probe preparation as described in previous works [6].…”
Section: Introductionmentioning
confidence: 96%
“…For example, the sterling standard stipulates a 7.5 % copper concentration. Unlike other precious metals such as gold and platinum, silver is known to tarnish with time forming Ag 2 S when exposed to low concentrations (<1 ppb) of H 2 S in ambient environments [1][2][3]. While Ag 2 S is the main component in silver tarnish, sulfate, chloride, oxide, and oxygenated carbon species can also be present [4].…”
Section: Introductionmentioning
confidence: 99%